Recycling cooperation and buying status - Pinto, Diego Costa (2019)
Pinto, D. C., Maurer Herter, M., Rossi, P., Meucci Nique, W., & Borges, A. (2019). Recycling cooperation and buying status: Effects of pure and competitive altruism on sustainable behaviors. European Journal Of Marketing, 53(5), 944-971. https://doi.org/10.1108/EJM-09-2017-0557 ---%ABS3%